IMPLEMENTASI SUPPLY CHAIN MANAGEMENT PADA TOKO ALAT-ALAT OLAH RAGA BERBASIS WEB. STUDI KASUS PADA DODI SPORT - Aep Suryaman; Agus Wahyudin; Dadan Nugraha (NUANSA INFORMATIKA, 2018)
Supply Chain Management (SCM) is a set of methods which is applied and integrated for suppliers, employers, warehouses and other storage areas effectively and efficiently. This study aims to facilitate the management of goods stock, starting from the process of ordering good from suppliers, supplying goods until managing the goods to the customers. Dodi Sport is a company in the field of sports equipment that sells products such as, pants, jersey shirts, shoes, bags, ball and other sport equipments. The company is located in at Ciamis Street number 97 Windujanten Kadugede – Kuningan. The system created uses Rational Unified Process (RUP) method, web-base system design and using supporting applications such as XAMPP, the design programming language using Hypertext Preprocessor (PHP) language and the design user interface and DBMS (Database Management System) uses MySQL, this application helps companies to store data management of goods, ordering, purchasing, sales, returning goods and others that still uses manual system, or not computerized yet with the aim of maximizing the performance and also profits for the company, suppliers, including end customers. It is expected to provide satisfaction to suppliers and companies so that running the business process will be easy.Keywords : Web, RUP, SCM, Dodi Sport Kuningan